Soil-erosion research on the determination of the degree of potential hazards of mining-brown stepped soils of the Quba-Khachmas zone in Azerbaijan - Aliev Z. G. (Interactive science, 2017)
on the plots under sowing of field crops traits for which you can define the degree of soil erosion are projective cover and height plants. Enthusiastically steepness of slopes the possibility of using cultivated crops as indicators of soil erosion is reduced. The degree of soil erosion of natural grassland can be estimated based on existing dependencies between the grass plants and extent of soil erosion. Pretty strong erosion of soils of sloping meadows can be recognized for environmental regimes of vegetation habitats.
Keywords: эрозия; чернозём; биоклиматический; ступенчатый; erosion; humus; bio-climatic; stepped